Theory and practice for the early childhood education: Formative needs (Revista Contexto & Educação, 2024)
In this essay, we aim to discuss teacher training as a scenario to initiate and strengthen the necessary changes in early childhood education, guaranteed by the Law of Directives and Bases for Education, in 1996, based on research carried out by the group over the last 20 years. We believe that to have a qualified practice, it is necessary to work collectively on initial and continued education, considering the place of action and the particular demands of this context. We resorted to the analysis of researches in the area that provided data on how this context influences and is influenced by formation. We argue that to change the current educational landscape with babies, it is necessary to invest in teacher learning, proposing changes in the training curriculum to include content related to child development, the activities performed in the educational context, and the teacher's power to intentionally plan and organize meaningful experiences for the child.
Keywords: Teacher training; Early childhood education; Nursery